2014
DOI: 10.1089/vbz.2013.1359
|View full text |Cite
|
Sign up to set email alerts
|

Anjozorobe Hantavirus, a New Genetic Variant of Thailand Virus Detected in Rodents from Madagascar

Abstract: Until now, there was only serological evidence that hantaviruses were circulating in rodents and infecting humans from Madagascar. To assess the presence of a hantavirus on the island, between October, 2008, and March, 2010, we sampled 585 rodents belonging to seven species in the Anjozorobe-Angavo forest corridor, 70 km north from the capital city Antananarivo. A hantavirus was detected from organs of the ubiquist roof rat (Rattus rattus) and of the endemic Major's tufted-tailed rat (Eliurus majori). Amazingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Eight strains were determined for genome sequences, and three strains were selected for sequencing of partial L, M, and S. The complete genome sequence (including non-coding regions (NCRs)) of these viruses showed more than 93.5% nucleotide (nt) identity with each other, suggesting that they all belonged to the same viral species. The open reading frame (ORF) for L of this species showed 79%-81.4% nt identity with those of Anjozorobe HanVs detected in R. rattus and Eliurus majori from Madagascar in 2014 [43], the M and S ORFs of this species showed 95%-96% and 96.1%-99.4% nt identities with those of Thailand virus strains found in B. indica of Thailand in 1994 and 2004 [44,45] (Table S5). Phylogenetic trees based on the complete M segment-encoded glycoprotein precursor (GPC), L segment-encoded RNA-dependent RNA polymerase (RdRp), and S segment-encoded nucleocapsid protein (N) amino acid sequences were constructed (Figure 3).…”
Section: Characteristics Of Negative-stranded Rna Virusesmentioning
confidence: 93%
“…Eight strains were determined for genome sequences, and three strains were selected for sequencing of partial L, M, and S. The complete genome sequence (including non-coding regions (NCRs)) of these viruses showed more than 93.5% nucleotide (nt) identity with each other, suggesting that they all belonged to the same viral species. The open reading frame (ORF) for L of this species showed 79%-81.4% nt identity with those of Anjozorobe HanVs detected in R. rattus and Eliurus majori from Madagascar in 2014 [43], the M and S ORFs of this species showed 95%-96% and 96.1%-99.4% nt identities with those of Thailand virus strains found in B. indica of Thailand in 1994 and 2004 [44,45] (Table S5). Phylogenetic trees based on the complete M segment-encoded glycoprotein precursor (GPC), L segment-encoded RNA-dependent RNA polymerase (RdRp), and S segment-encoded nucleocapsid protein (N) amino acid sequences were constructed (Figure 3).…”
Section: Characteristics Of Negative-stranded Rna Virusesmentioning
confidence: 93%
“…2a, b), following the methodology described above. This analysis showed that MAYOV clusters within the Thailand hantavirus clade closer to the isolates circulating in the Indian Ocean, South-East Asia (Hugot et al, 2006;Plyusnina et al, 2009;Johansson et al, 2010) and Madagascar (Reynes et al, 2014), rather than the Murinae-associated hantaviruses circulating in continental Africa (Klempa et al, 2006(Klempa et al, , 2012Witkowski et al, 2014). The data suggested that both MAYOV and Anjozorobe virus, the closest variant within the Thailand hantavirus clade, may have resulted from a westward expansion of an ancestral South-East Asian hantavirus introduced with R. rattus (Cheke & Hume, 2008;Tollenaere et al, 2010).…”
mentioning
confidence: 91%
“…Although relatively few hantavirus studies have been carried out in Africa and the surrounding regions, since 2006 eight hantaviruses have been [ 14 ] identified in rodents, insectivores and bats in mainland Africa [ 17 24 ] whilst recently two hantaviruses were detected in the Indian Ocean region [ 25 , 26 ]. The two hantaviruses found in the Indian Ocean region both belonged to Thailand orthohantavirus (THAIV) specie which was primarily found in Southeast Asia [ 27 ].…”
Section: Introductionmentioning
confidence: 99%